Evaluation of the efficiency and safety in cosmetic products - Uckaya, Meryem; UÇKAYA, FATİH; UÇKAYA, FATİH; DEMİR, NAZAN; DEMİR, YAŞAR (My University, 2016)
Chemicals used in cosmetics have to interact with enzymes for beneficial or destroy purpose after they enter in our body. Active sections of enzymes that catalyze reactions have three dimensions and they are active optically. When these limitations of catalytic sections are considered, it may be considered that defining geometric specifications of chemical materials and functional groups they contain may contribute on safety evaluations of cosmetic products.